Review of the Completeness of the Medical Resume Form Based on the Assessment Elements of Mirm 15 National Hospital Accreditation Standards (SNARS) at Imelda Pekerja Indonesia Hospital Medan 2021 - Liem, John Barker; Rifhan, Zanurul; Simanjuntak, Marta; Sitorus, Mei Sryendang; Alna, Jihan (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Incompleteness in filling out a medical resume will greatly affect the hospital's accreditation assessment listed in the MIRM 15 SNARS standard sub-group Issue 1.1. This study aims to determine the completeness of filling out the resume form based on the assessment elements of MIRM 15 SNARS Edition 1.1 at Imelda Pekerja Indonesia Hospital in Medan. This study uses quantitative and qualitative methods, with a population of 1,355 medical resume forms at Imelda Pekerja Indonesia Hospital Medan in November-December 2021 and a sample of 93 medical resumes which are completed into 100 medical resume forms. Based on the results of the study, it was found that 76 medical resume forms were filled (70%) and 30 medical resume forms were incomplete (30%). score Based on the assessment of SNARS Edition 1.1, the number of complete medical resume forms was 76% with a score of 5 (partially fulfilled) because the achievement range was 29%-79%. The highest completeness on the medical resume form at Imelda Pekerja Indonesia Hospital is found in the patient history component, diagnostic examination, therapeutic procedures and actions, drugs given and drugs when the patient leaves the hospital, the patient's health condition (current status) and follow-up instructions (100% ) Medical resume forms and the lowest completeness were found on physical examination (15%) indication of patients being treated (6%), comorbidities (12) and patient/family signatures (24%) of medical resume forms. Researchers suggest that there is a need for socialization that continuously increases knowledge to medical officers about filling out the complete medical resume form according to SNARS at Imelda Pekerja Indonesia Hospital in Medan.